2007
DOI: 10.1016/j.jadohealth.2007.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Beliefs about Preferred Resources for Help Vary Depending on the Health Issue

Abstract: Background-Adolescents' health care use is less than ideal, especially for more sensitive services. We know little about adolescents' preferred resources for help for health-related issues, and whether these resources vary by problem type. This study examined whether adolescents' preferred resources for help differed depending on the health issue studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…This is consistent with past research on adolescent attitudes about help-seeking behavior for health issues, which found that adolescents preferred help from different sources depending on age, gender, and the healthcare issue being discussed [9,10]. Similarly, parental awareness of vaccination and consent for vaccination were important to adolescents in our survey.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with past research on adolescent attitudes about help-seeking behavior for health issues, which found that adolescents preferred help from different sources depending on age, gender, and the healthcare issue being discussed [9,10]. Similarly, parental awareness of vaccination and consent for vaccination were important to adolescents in our survey.…”
Section: Discussionsupporting
confidence: 92%
“…2 Interventions delivered by primary health care providers can also play an important role in prevention and cessation. 1,2,7 Research suggests that adolescents view physicians as a preferred source of smoking cessation information, 8,9 and between 68% and 84% of adolescents under age 18 years report seeing a doctor at least annually. 3,10 Accordingly, a number of national guidelines recommend that health care providers offer adolescents tobacco use screening, education, and counseling during theirannual visit.…”
mentioning
confidence: 99%
“…Norcross et al (1996) reported that among adult patients, those who were married were more likely than unmarried patients to be influenced to seek health care by a member of the opposite sex; with more male patients following this pattern than female patients. Another study showed that in addition to citing mothers as top sources of health care information (Ackard & Neumark-Sztainer, 2001;Aten, Siegel, & Roghmann, 1996), adolescents cited romantic partners and friends as important sources of health information about sex (Marcell & Halpern-Felsher, 2007). A third study showed that mother's influence on her adolescent's tendency to seek medical care persisted as a main effect after controlling for sex, age, race, birth order, socioeconomic status, and intellectual ability (Fox, 1991).…”
mentioning
confidence: 99%